Configurational entropy of black hole quantum cores - Casadio, R. (2023)
Two types of information entropy are studied for the quantum states of a model for the matter core inside a black hole geometry. A detailed description is first given of the quantum mechanical picture leading to a spectrum of bound states for a collapsing ball of dust in general relativity with a non-trivial ground state. Information entropies are then computed, shedding new light on the stability of the ground state and the spectrum of higher excited states.